Physical Effects of Variable Fluid Properties on Laminar Gas Microconvective Flow. Issue 7 (7th February 2017) - Kumar, Rajan; Mahulikar, Shripad P.
Abstract: The physical effects of variable fluid properties on heat transfer and frictional flow characteristics of laminar gas microconvective flow are investigated in this research. The fully developed flow through a microtube is studied numerically by using 2D continuum‐based governing equations. The physical effects induced due to variations in gas density with pressure and temperature, and gas viscosity, thermal conductivity, and specific heat with temperature are analyzed. Numerical results reveal that the heat transfer and frictional flow characteristics of laminar gas microflow are drastically affected by these physical effects. Hence, this research suggests that these physical effects need to be well considered in the applications of laminar gas microconvection based on large temperature gradients, for example, the design of microchannel heat sinks, and the flow cannot be generally considered as a constant property flow, as in conventional channels.